1995
DOI: 10.1128/iai.63.1.280-288.1995
|View full text |Cite
|
Sign up to set email alerts
|

Noninhibitory binding of human interleukin-2-activated natural killer cells to the germ tube forms of Candida albicans

Abstract: During incubation in vitro with yeast or germ tube forms of Candida albicans, only 2 to 6% of freshly isolated human natural killer (NK) cells (>85% CD16 ؉ , CD56 ؉ , CD3 ؊ ; <15% CD3 ؉ ; cytolytic for the NK-susceptible target K562 but not for the NK-resistant target DAUDI), were seen to interact with the fungal cells. As seen under the electron microscope, the contact area had a limited extent and was narrow, and neither the surface nor the intracytoplasmic organization of the NK cell was altered. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This may argue for the presence of another pump (we demonstrated CDR gene overexpression) or a completely different mechanism affecting both fluconazole resistance and virulence, as was demonstrated in these isolates (12). Changes in ligands for phagocyte receptors, potential to elicit cytokine production, morphotype, phospholipases, or other factors could account for altered virulence of some isolates (2,3,8,10,13).…”
Section: Discussionmentioning
confidence: 60%
“…This may argue for the presence of another pump (we demonstrated CDR gene overexpression) or a completely different mechanism affecting both fluconazole resistance and virulence, as was demonstrated in these isolates (12). Changes in ligands for phagocyte receptors, potential to elicit cytokine production, morphotype, phospholipases, or other factors could account for altered virulence of some isolates (2,3,8,10,13).…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, NK-depleted mice with severe combined immunodeficiency did not show enhanced susceptibility to systemic C. albicans infection (45). Although NK cells lack direct candidacidal capacity (46,47), these cells can activate phagocytes by secreting IFNγ (48,49). Interestingly, C. albicans suppresses NK cell function via induction of myeloid-derived suppressor cells, thus questioning the functional stability of NK cells in this system (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, macrophages are considered to be important as a mechanism of CD4 Th1‐type defenses and PMNL certainly infiltrate into mucosal tissues. Natural killer cells, on the other hand, are not considered to be effective against Candida (Djeu and Blanchard, 1987; Arancia et al , 1995). Despite the potential role for PMNL against Candida at mucosal sites, studies in animals have not revealed a role for them at the vaginal mucosa.…”
Section: Host Defense Mechanisms Against C Albicansmentioning
confidence: 99%